2021
DOI: 10.1016/j.euros.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Initial Observation of a Large Proportion of Patients Presenting with Clinical Stage T1 Renal Masses: Results from the MUSIC-KIDNEY Statewide Collaborative

Abstract: Background While surgical excision remains the principal management strategy for clinical T1 renal masses (cT1RMs), the rates of noninterventional approaches are not well known. Most single-institution and population-based series suggest rates below 10%. Objective To evaluate the use of observation for newly diagnosed cT1RM patients in academic and community-based practices across a statewide collaborative. Design, setting, and participants T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…One might expect that older patients and those with lower renal function would be more likely to undergo RMB since they are less likely to proceed straight to intervention. Our findings do not support this assumption and might be attributable to the high rate of initial observation in our cohort of almost 50% [8] , which is frequently offered to such patients without up-front RMB [28] . The high rate of observation is an important feature of the treatment pattern for cT1 RM within MUSIC-KIDNEY, with predictors of noninterventional management including lesion type (Bosniak III–IV > solid; p = 0.017), tumor stage (T1a vs T1b; p < 0.001), and higher age ( p < 0.001) [28] .…”
Section: Discussioncontrasting
confidence: 77%
“…One might expect that older patients and those with lower renal function would be more likely to undergo RMB since they are less likely to proceed straight to intervention. Our findings do not support this assumption and might be attributable to the high rate of initial observation in our cohort of almost 50% [8] , which is frequently offered to such patients without up-front RMB [28] . The high rate of observation is an important feature of the treatment pattern for cT1 RM within MUSIC-KIDNEY, with predictors of noninterventional management including lesion type (Bosniak III–IV > solid; p = 0.017), tumor stage (T1a vs T1b; p < 0.001), and higher age ( p < 0.001) [28] .…”
Section: Discussioncontrasting
confidence: 77%
“…While there is clearly selection bias in the cases submitted to the VTB, this is consistent with our previously reported high rate of AS across MUSIC. 16…”
Section: Discussionmentioning
confidence: 99%
“…For patients undergoing PN, the regular use of ultrasound during planning and resection of endophytic tumours, potential use of three‐dimensional models for more complex tumours, and referral of more challenging cases to higher volume surgeons may improve PSM rates. Further, within the MUSIC‐KIDNEY we have reported that active surveillance is commonly applied to patients with cT1RM, including any patient with a tumour of <2 cm, and for selected patients with larger tumours, finding this approach to be safe and effective [6]. Most importantly, we hope this report of the initial steps MUSIC‐KIDNEY has taken to address PSM rates with PN will help encourage urological surgeons to critically consider the elements of their surgical approach, refine their technical skills, and consequently achieve an improved PSM rate.…”
Section: Variable All Ct1rm Patients Undergoing Pn Psm P No Yesmentioning
confidence: 99%
“…The Michigan Urological Surgery Improvement Collaborative-Kidney mass: Identifying and Defining Necessary Evaluation and therapY (MUSIC-KIDNEY) is a statewide quality improvement (QI) initiative focused on improving care for patients with clinical stage T1 renal masses (cT1RM) [6]. The MUSIC-KIDNEY offers a unique opportunity to evaluate and improve rates of PSM by use of specific QI interventions discussed at regular collaborative-wide meetings.…”
mentioning
confidence: 99%